2016
DOI: 10.1038/srep29050
|View full text |Cite
|
Sign up to set email alerts
|

The upper respiratory tract microbiome and its potential role in bovine respiratory disease and otitis media

Abstract: The upper respiratory tract (URT) hosts a complex microbial community of commensal microorganisms and potential pathogens. Analyzing the composition and nature of the healthy URT microbiota and how it changes over time will contribute to a better understanding of the pathogenesis of pneumonia and otitis. A longitudinal study was conducted including 174 Holstein calves that were divided in four groups: healthy calves, calves diagnosed with pneumonia, otitis or both diseases. Deep pharyngeal swabs were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
126
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(148 citation statements)
references
References 56 publications
16
126
3
3
Order By: Relevance
“…Although there was considerable inter-individual variability, many of the relatively abundant genera found in the NP microbiota of the current study were also identified previously as being among the most relatively abundant in the NP of feedlot [1,3] and dairy cattle [35]. In addition, of the 20 most relatively abundant genera, Acinetobacter, Bacillus, Corynebacterium, Mannheimia, Moraxella, Pasteurella, Proteus, Psychrobacter, and Streptococcus have all been isolated from the bovine Cattle were sampled at a ranch (Day 0) prior to shipping to a feedlot and then 2, 7, and 14 days after feedlot placement nasopharynx using culture-based methods [1,5,39].…”
Section: The Bovine Nasopharyngeal Microbiotasupporting
confidence: 74%
See 1 more Smart Citation
“…Although there was considerable inter-individual variability, many of the relatively abundant genera found in the NP microbiota of the current study were also identified previously as being among the most relatively abundant in the NP of feedlot [1,3] and dairy cattle [35]. In addition, of the 20 most relatively abundant genera, Acinetobacter, Bacillus, Corynebacterium, Mannheimia, Moraxella, Pasteurella, Proteus, Psychrobacter, and Streptococcus have all been isolated from the bovine Cattle were sampled at a ranch (Day 0) prior to shipping to a feedlot and then 2, 7, and 14 days after feedlot placement nasopharynx using culture-based methods [1,5,39].…”
Section: The Bovine Nasopharyngeal Microbiotasupporting
confidence: 74%
“…In agreement with previous work on the bovine NP microbiota, the bacterial phyla Proteobacteria, Firmicutes, Tenericutes, and Actinobacteria were relatively Cattle were sampled at a ranch (Day 0) prior to shipping to a feedlot and then 2, 7, and 14 days after feedlot placement. The percent variation explained by the principal coordinates is indicated on the axes abundant at all sampling times [1][2][3]35]. One of the more surprising findings was the detection of Euryarchaeota 16S rRNA gene sequences at an overall relative abundance of 1.8%.…”
Section: The Bovine Nasopharyngeal Microbiotamentioning
confidence: 98%
“…Bovine respiratory disease (BRD) is an important problem in cattle production that remains responsible for economic losses in dairy and feedlot herds because of high morbidity and mortality rates . It is observed in young calves, particularly between 2 and 6 weeks of age . In addition, BRD negatively impacts growth, reproductive performance, and longevity …”
mentioning
confidence: 99%
“…[1][2][3] It is observed in young calves, 4 particularly between 2 and 6 weeks of age. 5,6 In addition, BRD negatively impacts growth, reproductive performance, and longevity. 5,7 Mycoplasma spp.…”
mentioning
confidence: 99%
“…Conventional PCR is problematic because pathogens can be present in both healthy and diseased calves. In other situations with multiagent diseases with opportunistic pathogens, quantification of the pathogens in clinical specimens has added substantially to the value of microbiological diagnosis (Lima et al, 2016;Pedersen et al, 2014Pedersen et al, , 2013. Recently, a multiplex quantitative PCR (qPCR) method to detect relevant bacterial pathogens of BRD was published, demonstrating better performance than culture in co-infections with two or more pathogens (Loy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%